The Total Cost of the Sterilisation of Materials Used During Surgery for Postpartum Haemorrhage - Castiel, Didier; Bréchat , Pierre-Henri (Journal of Public Governance, 2021)
Objectives: The aim of this research paper is to determine the incomes and outgoings related to postpartum haemorrhage implementation for organisations which support prospective payment as the Diagnosis Related Groups (DRG) in United States. We have to take into account surgical costs associated with care provided for these specific patients. Among these costs, surgical acts have to be calculated in association with the sterilisation of materials which can be used more than once. Research Design & Methods: Patients’ evaluation has been held from data collected in obstetrical and sterilisation departments of a university hospital (in Paris), which provides surgical care. The research was based on data from 2014 and 2015. All estimated costs are seen from the hospital’s point of view. Surgical care is provided according to the following acts: manual exploration of the uterus (uterine cavity), exploration with valve, hysterectomy, caesarean scar, vaginal packing or unpacking, hypogastrium (iliac vascular ligation), and repair of other organs, such as bladder and embolisation. We take into account the sterilisation of materials used during surgical acts, as well as the staff which was involved in this study. Findings: 262 patients were taken care of with regard to postpartum haemorrhage, and 255 patient files were studied. Average age was 31.42 +/- 5.5 years old. The cost of surgical procedures goes from 275 EUR for uterus exploration to 875 EUR for hysterectomy. Cost per sterilisation cycle for material used during surgical procedures was about 100 E per cycle and about 33 E per act, no matter the nature of the act. Implications / Recommendations: The sterilisation of medical devices used in these interventions represents a significant part of the fixed cost: 7.5% to 11.4%. These results make it possible to elaborate one or more future DRGs’ “bleeding of the delivery”. Contribution / Value added: This study is an example showing that the current reforms do not favour the quality-of-care coverage. This can contribute to the strengthening and to the recognition of the coverage of postpartum haemorrhage as one of the first causes of maternal deaths, the reduction of which is a priority for public health, as well as a concern for the users. This study is also a contribution to managed care empowerment. Managed care helped to slow down the growth of health care expenditures.